Penerapan Teknologi Digital Dalam Pengelolaan Kelas di Sekolah Dasar - Rizqa Mardhiah; Primanita Sholihah Rosmana; Mutiah Amalia; Susanti Ariyanti; Faizal Zulfikar; Fadilah (STAI AL-AMIN, 2025)
The digital era has brought significant changes to the field of education, making technology an essential part of the teaching and learning process in elementary schools. This study aims to evaluate and improve classroom management in a digital learning context at Rosela Indah Public Elementary School. Using a descriptive qualitative method, data were collected through interviews with the fourth-grade homeroom teacher, classroom observations, and analysis of school documents. Data analysis involved reduction, presentation, and drawing conclusions. The results showed that the integration of digital technology enhances learning effectiveness and student engagement. Teachers play a key role in creating enjoyable and meaningful learning experiences through the use of self- developed learning applications. Digital learning also facilitates easier access to information, boosts students’ motivation, and encourages better interaction and collaboration. However, several challenges were identified, including increased workload for teachers and parents, inconsistent content quality, and risks related to students’ concentration and health. Effective strategies include the use of learning management applications and a point-based reward and punishment system. Achieving success in digital learning requires collaboration among teachers, students, parents, and sufficient technological support. This study recommends improving teachers’ digital competencies, developing a curriculum that supports digital approaches, involving parents, and conducting regular evaluations.